Physical, Financial, and Mental Readiness of Teenagers for Marriage Kesiapan Fisik, Finansial dan Mental Remaja untuk Menikah - Setyawati, Irni; Utami, Kusniyati; Soekmawaty Riezqy Ariendha, Dian (STIKES Yarsi Mataram, 2024)
Marriage is the physical and mental bond between a man and a womanas husband and wife with the aim of forming a happy and eternal familyaccording to God Almighty. The divorce rate in NTB is still relatively higheven though it has decreased from 2021-2023. Divorce can be causedby the physical, financial and mental unpreparedness of the couplebefore marriage. From the results of simple interviews with 10 studentsat Inkes Yarsi Mataram, 80% stated that they did not know aboutphysical, financial and mental readiness for marriage, and 20% ofstudents knew but little. From the results mentioned above, theresearcher is interested in conducting research on the physical, financialand mental readiness of adolescents to get married at Inkes YarsiMataram. This study used an observational survey design with a crosssectional time approach. This research was conducted in September2024 at Inkes Yarsi Mataram. The sample obtained was 204 people.Data analysis using univariate and multivariate analysis. The results ofthe study found that adolescents‘ desire to get married quickly causedthe highest physical readiness by 24.03 times higher than adolescents’mothers as housewives. Female gender caused the highest financialreadiness by 0.31 times. Adolescents who have boyfriends causemental readiness for marriage by 0.22 times. It is necessary to educatestudents about physical, financial and mental readiness for marriageboth through academic and student activities.Abstrak